2018
DOI: 10.1192/bjb.2018.67
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to using clozapine in treatment-resistant schizophrenia: systematic review

Abstract: Aims and methodTo systematically review the literature on barriers to the use of clozapine and identify any interventions for optimizing clozapine use in treatment-resistant schizophrenia. Journal databases were searched from 1972 to March 2018. The following search terms were used: treatment-resistant schizophrenia, clozapine, barriers, use, prescription rates, implementation, clozaril and prescribing practices. Following a review of the literature, 15 papers were included in the review.ResultsThe major barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 30 publications
4
126
1
2
Order By: Relevance
“…Clozapine (CLZ) is considered the double-edged sword antipsychotic drug, since CLZ is one of the most effective but toxic antipsychotics against antipsychotics-resistant schizophrenia [17]. In fact, despite causing myocarditis, cardiomyopathy, agranulocytosis, and seizures [18][19][20][21][22], CLZ remains the gold-standard antipsychotic for treatment-refractory schizophrenia and is the only approved medication licensed for this indication [17,23]. The mechanisms of clinical actions of CLZ against antipsychotics-resistant schizophrenia have been considered to be modulated by multimodal targets actions, including NMDAR and dopamine D2 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine (CLZ) is considered the double-edged sword antipsychotic drug, since CLZ is one of the most effective but toxic antipsychotics against antipsychotics-resistant schizophrenia [17]. In fact, despite causing myocarditis, cardiomyopathy, agranulocytosis, and seizures [18][19][20][21][22], CLZ remains the gold-standard antipsychotic for treatment-refractory schizophrenia and is the only approved medication licensed for this indication [17,23]. The mechanisms of clinical actions of CLZ against antipsychotics-resistant schizophrenia have been considered to be modulated by multimodal targets actions, including NMDAR and dopamine D2 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…This underutilization responds to barriers related to the perceived burden of treatment, as well as clinicians' lack of familiarity with the use of clozapine . While there is a large body of literature on safety and efficacy of clozapine , to date there are few recommendations to clinicians on how to apply this research in clinical practice, particularly in the face of the prescription barriers . In this narrative review, we consider data from randomized controlled trials, prescription registries, and patient and prescriber surveys to generate practical and actionable recommendations for clinicians.…”
mentioning
confidence: 99%
“…This mismatch between evidence‐based recommendations and practice in the real world results in suboptimal treatment for individuals with severe mental illness, with important implications for societal burden, and individual morbidity and mortality. This underutilization responds to barriers related to the perceived burden of treatment, as well as clinicians' lack of familiarity with the use of clozapine . While there is a large body of literature on safety and efficacy of clozapine , to date there are few recommendations to clinicians on how to apply this research in clinical practice, particularly in the face of the prescription barriers .…”
mentioning
confidence: 99%
“…It has also been shown that in first episode schizophrenia the response rate to a second antipsychotic drops dramatically then increases again with clozapine, suggesting that second-line use of clozapine may well be more appropriate than third line [16]. There are many reported barriers to clozapine prescribing, including concerns over need for blood testing and potential for side-effects but also clinician and patient attitudes to clozapine [89][90][91]. Recent authors have highlighted the need to review stringent blood monitoring requirements for clozapine, which can lead to unnecessary treatment discontinuation [92].…”
Section: Discussionmentioning
confidence: 99%